Job Satisfaction Of The Millennial Generation Is Based On Leadership Style: A Systematic Literature Review - Duki Adam; Ade Irma Anggraeni (Citakonsultindo, 2024)
The aim of this research is to find out the role of leadership style in the performance and job satisfaction of the millennial generation. The Systematic Literature Review (SLR) method was used in this research. The review process begins with collecting 350 articles from the Google Scholar, DOAJ, and Science Direct databases, where in the final stage there are 21 journals that will go through a further analysis process. The results show that the role of strong leadership style in encouraging increased performance of millennial employees was found. The influence of effective leadership style on job satisfaction of the millennial generation can also be observed. Millennials tend to look for leaders who can provide direction, support and positive feedback in their work.